UJI ANTIOKSIDAN DAUN MUDA DAN DAUN TUA GAHARU (Aquilaria malaccensis Lamk) BERDASARKAN PERBEDAAN TEMPAT TUMBUH POHON - Rizki khadijah Harahap; Ridwanti Batubara; Surjanto Surjanto (Program studi Kehutanan USU, 2015)
The leaf of aloe has an antioxidant activity which can reduce free radicals. The research of aloe toward chemical compund of fresh and rotten leaf, and its antioxidant activities. Ethanol extract the leaf o aloe by using maceration method, concentrated by rotary evaporator and evaporated by waterbath. The test of antioxidant activity use DPPH method 1,1- diphenil-2-picrylhydrazil (DPPH), and an observed parameter is the percentage of free- radical-reduction in 30th minute with different concentrations (40ppm, 60ppm, 80ppm, 100ppm ) and value of IC50 ( Inhubitory concentrations) is analyzed by using regressions equation. The of EESDG show the percentage of muffled- fresh-research leaf from arboretum of usu (Univercity of north sumatera) is higher as the entianceluent of concentration sample ;92,10% ; 92,10%; 93,80%; 93,80%; and the lowest percentage down to 22,26%; 25,31%; 27,94%; 35,72%. And result of antioxidant activity by using light of spectrophotometer is catched on the wave of 516 nm, and get the result that (EESDG) fresh and rotten leaf from Langkat has IC50 of 39,70 ppm and 40,03ppm. While fresh and rotten leaf from Arboretum of USU has IC50 of 28,50 and 43,20 ppm. The research result that the estracts of ethanol and simplisia aloe have a very strong antioxidant activity.Keywords:. gaharu leaf,ethanol extract, antioxidant activity